2022
DOI: 10.3390/agronomy12081978
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of GASA Gene Family in Ten Cucurbitaceae Species and Expression Analysis in Cucumber

Abstract: Gibberellic acid-stimulated in Arabidopsis (GASA), a unique small molecular protein of plants, plays an essential role in plant growth and development. The GASA family genes have been identified and studied in many plants. However, the identification of GASA gene family in Cucurbitaceae species has not been reported yet. Therefore, in this study, based on the available genome information on the Cucurbitaceae species, the GASA family genes in 10 Cucurbitaceae species including cucumber (Cucumis sativus), waterm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…The GASA family has been reported to be differentially expressed in different organs as well as in diverse abiotic stresses and hormones [ 4 , 38 , 39 ]. Expression analysis of lettuce organs showed that six LsGASA were expressed in the leaves, roots, seeds, stems, and flowers (Additional file 5 : Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The GASA family has been reported to be differentially expressed in different organs as well as in diverse abiotic stresses and hormones [ 4 , 38 , 39 ]. Expression analysis of lettuce organs showed that six LsGASA were expressed in the leaves, roots, seeds, stems, and flowers (Additional file 5 : Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the authors extracted peptides from the medium of a whole plant in submerged culture using o-chlorophenol and detected an uncharacterized small, secreted peptide gene family in Arabidopsis . Other research teams have focused on specific small peptide families in noncereal crops; for instance, genome-wide analyses have led to identification of CLE in Malus × domestica (apple), the GASA family in Cucumis sativus (cucumber), and the defensin family in Arachis hypogaea L. (peanut) (Zhang et al 2022a , 2022b ; Zhao et al 2022 ).…”
Section: Experimental Strategies For Studying Plant Small Peptidesmentioning
confidence: 99%
“…Our understanding of the signaling cascades initiated by adverse environmental phenomena has increased owing to the identification of several gene families in the model plant Arabidopsis thaliana L., where GASA (Gibberellic acid-stimulated Arabidopsis ) is one of those proteins (also referred to as Snakin protein) with an array of cysteine-rich (Cys) peptides regulated by gibberellins (GAs) [ 1 , 2 , 3 , 4 , 5 , 6 ]. In recent years, the number of studies that have focused on a cysteine-rich protein that plays a role in the development and biotic and abiotic stress tolerance in a wide range of plants has increased [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. To date, GASA peptides were identified in diverse monocotyledonous and dicotyledonous plant species [ 18 ].…”
Section: Introductionmentioning
confidence: 99%